2018
DOI: 10.1002/cncr.31659
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction in young adults with cancer and the role of sociodemographic, medical, and psychosocial factors: Results of a longitudinal study

Abstract: Of all the variables examined, social support was found to be the most decisive factor associated with LS at both time points. With regard to LS, social support and adjustment to illness should be given more consideration in the medical care of AYA patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
2
25
0
3
Order By: Relevance
“…One RCT and another pre-post study found that mHealth social support program was associated with an improved HRQoL of cancer patients ( Zhu et al, 2018 ; Pappot et al, 2019 ; Cella et al, 1993 ). Perceived social support is an important determinant of life satisfaction, better mood symptoms, and better perceived HRQoL of patients with cancer ( Leuteritz et al, 2018 ; Yoo et al, 2017 ). Coping strategies of cancer patients are important for the HRQoL of cancer patients ( Nipp et al, 2016 ) and can mediate the relationship between social support and HRQoL ( Zhou et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…One RCT and another pre-post study found that mHealth social support program was associated with an improved HRQoL of cancer patients ( Zhu et al, 2018 ; Pappot et al, 2019 ; Cella et al, 1993 ). Perceived social support is an important determinant of life satisfaction, better mood symptoms, and better perceived HRQoL of patients with cancer ( Leuteritz et al, 2018 ; Yoo et al, 2017 ). Coping strategies of cancer patients are important for the HRQoL of cancer patients ( Nipp et al, 2016 ) and can mediate the relationship between social support and HRQoL ( Zhou et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…This instrument evaluates the respondent's subjective QoL. It has been used in several medical elds such as cancer [24][25][26], orthopedics [27], and psychiatry [28]. The questionnaire covers eight areas of life that are assumed to be relevant for most people in the 8) Partnership/Sexuality.…”
Section: Questions On Life Satisfaction (Flz-m)mentioning
confidence: 99%
“…91 When compared with other cancer types, higher, lower and similar HRQoL scores were found depending on the comparison groups. [92][93][94][95] Most prevalent symptoms during chemotherapy in either curative or palliative setting were fatigue, lack of appetite and drowsiness. 96 Pain was prevalent in over half of patients with sarcoma.…”
Section: Metastatic Sarcomamentioning
confidence: 99%